Who Europeanises parliamentary attention, on which issues and how? A policy agenda perspective. Issue 4 (2nd October 2017) - Gava, Roy; Sciarini, Pascal; Varone, Frédéric
ABSTRACT: This paper contributes to the literature on the Europeanisation of national parliaments by looking at the behavioural dimension of Europeanisation in the Swiss parliament. The authors examine the differences in parliamentary interventions on EU-related issues over time, between types of instruments (agenda-setting versus control) and across parties. Moreover, the authors measure the attention devoted to various policy issues and the tone of parliamentary interventions. Empirically, they analyse with descriptive statistical tools EU-related parliamentary interventions introduced in the Swiss parliament over 30 years (1984–2014). Results show that parliamentary attention to the EU is strongly influenced by the activism of the Swiss People's Party, a Eurosceptic member of the Swiss governing 'coalition'.